Delivery Indications at Late-Preterm Gestations and Infant Mortality Rates in the United States - Reddy, Uma M. (2009)
OBJECTIVE: The rate of preterm births has been increasing in the United States, especially for births 34 to 36 weeks of gestation (late preterm), which now constitute 71% of all preterm births. The causes for these trends remain unclear. We characterized the delivery indications for late preterm births and their potential impact on neonatal and infant mortality rates. PATIENTS AND METHODS: Using the 2001 US Birth Cohort Linked birth/death files of 3 483 496 singleton births, we categorized delivery indications as follows: (1) maternal medical conditions; (2) obstetric complications; (3) major congenital anomalies; (4) isolated spontaneous labor: vaginal delivery without induction and without associated medical/obstetric factors; and (5) no recorded indication. RESULTS: Of the 292 627 late-preterm births, the first 4 categories (those with indications and isolated spontaneous labor) accounted for 76.8%. The remaining 23.2% (67 909) were classified as deliveries with no recorded indication. Factors significantly increasing the chance of no recorded indication were older maternal age; non-Hispanic, white mother; ≥13 years of education; Southern, Midwestern, and Western region; multiparity; or previous infant with a ≥4000-g birth weight. The neonatal and infant mortality rates were significantly higher among deliveries with no recorded indication compared with deliveries secondary to isolated spontaneous labor but lower compared with deliveries with an obstetric indication or congenital anomaly. CONCLUSIONS: A total of 23% of late preterm births had no recorded indication for delivery noted on birth certificates. Patient factors may be playing a role in these deliveries. It is concerning that these infants had higher mortality rates compared with those born after spontaneous labor at similar gestational ages. Given the excess risk of mortality, patients and providers need to discuss the risks of delivering a pre-term infant in the absence of medical indications at 34 to 36 weeks.